2021
DOI: 10.3897/bdj.9.e59001
|View full text |Cite
|
Sign up to set email alerts
|

One new species and one new record of Zasmidium in China

Abstract: Two hyphomycetous species were collected from leaves of Smilax china (Liliales, Smilacaceae) and Cremastra appendiculata (Asparagales, Orchidaceae). ITS barcoding indicated that they belong to the genus Zasmidium. Morphological data in combination with molecular phylogenetic analyses based on ITS, LSU and rpb2 confirmed that our Chinese strains represented a new species, Zasmidium liboense and a new record of Z. citri-griseum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 583 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…We obtained a highly similar match (98.7% nucleotide identity) to Zasmidium syzygii (NR_111826.1), supporting that the assembled isolate belongs to the Zasmidium genus. In line with this finding, previous studies have found Zasmidium isolates on symptomatic banana leaves (Arzanlou et al, 2008;Crous et al, 2021), and other Zasmidium species are reported to cause leaf spot diseases on other plant species such as citrus (Aguilera-Cogley et al, 2017;An et al, 2021;Han et al, 2015). The Zasmidium genome assembly we report here is less fragmented and 4 Mb larger than the previous genome assembly of a Zasmidium species; Z. cellare.…”
Section: The Assembled Genome Sequence Reveals That Isolate P124 Belo...supporting
confidence: 90%
“…We obtained a highly similar match (98.7% nucleotide identity) to Zasmidium syzygii (NR_111826.1), supporting that the assembled isolate belongs to the Zasmidium genus. In line with this finding, previous studies have found Zasmidium isolates on symptomatic banana leaves (Arzanlou et al, 2008;Crous et al, 2021), and other Zasmidium species are reported to cause leaf spot diseases on other plant species such as citrus (Aguilera-Cogley et al, 2017;An et al, 2021;Han et al, 2015). The Zasmidium genome assembly we report here is less fragmented and 4 Mb larger than the previous genome assembly of a Zasmidium species; Z. cellare.…”
Section: The Assembled Genome Sequence Reveals That Isolate P124 Belo...supporting
confidence: 90%
“…Notes — Zasmidium pearceae has well-developed stromata and smooth conidia, which differentiate it from other species of Zasmidium on Smilacaceae ( Archana et al 2014 , Braun et al 2014 , An et al 2019 ).…”
mentioning
confidence: 99%
“…Didymellaceae was established by De Gruyter et al (2009) with Didymella as the type genus. It is the largest family in the Pleosporales and accommodates more than 5400 taxon names (Crous et al 2004), including saprobic, endophytic and pathogenic species (Aveskamp et al 2008, Aveskamp et al 2010, Marin-Felix et al 2017. A great part of Didymellaceae species are reported as plant pathogens, which cause severe economic losses to many crops (Aveskamp et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It is the largest family in the Pleosporales and accommodates more than 5400 taxon names (Crous et al 2004), including saprobic, endophytic and pathogenic species (Aveskamp et al 2008, Aveskamp et al 2010, Marin-Felix et al 2017. A great part of Didymellaceae species are reported as plant pathogens, which cause severe economic losses to many crops (Aveskamp et al 2008). Recently, Didymellaceae was revised, based on morphological and phylogenetic analyses of ex-type sequences of LSU, ITS, rpb2 and tub2 loci, resulting in 19 genera (Chen et al 2015, Chen et al 2017, Currently, 37 genera are accepted (Wijayawardene et al 2017, Wijayawardene et al 2020, Valenzuela-Lopez et al 2018, Hou et al 2020a, Hou et al 2020b.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation